2006
DOI: 10.2143/ac.61.5.2017770
|View full text |Cite
|
Sign up to set email alerts
|

Role of myocardial bridging in the apical localization of stress cardiomyopathy

Abstract: Our data suggest that myocardial bridging possibly enhanced by catecholamines during stress may contribute, in association with left ventricular hypertrophy, to the preferential apical localization of the apical ballooning syndrome. Further investigations are necessary to confirm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…This observation is not compatible with the hypothesis that catecholamine-induced endothelial and/or microvascular toxicity might be an important pathophysiological component of Tako-Tsubo cardiomiopathy. In contrast, the presence of a myocardial bridge, possibly associated with focal abnormalities in the myocardial architecture [4], was described in previous case reports [5]. This characteristic, also present in our patient, might help explain why the akinesia is limited to the apical segments of the left ventricle in this condition.…”
Section: Dear Sirsupporting
confidence: 49%
“…This observation is not compatible with the hypothesis that catecholamine-induced endothelial and/or microvascular toxicity might be an important pathophysiological component of Tako-Tsubo cardiomiopathy. In contrast, the presence of a myocardial bridge, possibly associated with focal abnormalities in the myocardial architecture [4], was described in previous case reports [5]. This characteristic, also present in our patient, might help explain why the akinesia is limited to the apical segments of the left ventricle in this condition.…”
Section: Dear Sirsupporting
confidence: 49%
“…11 studies from Asia [18][19][20][21][22][23][24][25][26][27][28] contributed 249 patients (44.2%), 14 studies from Europe [29][30][31][32][33][34][35][36][37][38][39][40][41][42] 231 patients (41.0%), and 3 studies from North America [43][44][45] 83 patients (14.7%). Twelve studies were performed prospectively [20,23,25,27,[30][31][32]35,38,41,43,44], seven studies reported retrospective data [19,21,22,24,28,33,34] and nine studies were unspecified [18,26,29,…”
Section: Resultsmentioning
confidence: 99%
“…Transient prolonged QT intervals were consistently described in TLVABS. Mean/median QTc in seven studies [20,22,28,31,39,40,43] was ranging from 445.8 to 542 ms. Mental stress and autonomic changes have been demonstrated to precipitate prolongation of ventricular repolarization duration [46] and prolong QT interval [47], respectively.…”
Section: Electrocardiographic Datamentioning
confidence: 99%
See 2 more Smart Citations